Structural Composition of First-Neighbor Shells in GeSe2 and GeSe4 Glasses from a First-Principles Analysis of NMR Chemical Shifts - Kibalchenko, M; Yates, JR; Massobrio, C; Pasquarello, A (2011)
Isotropic chemical shifts and quadrupole coupling parameters of 77Se and 73Ge nuclei in GeSe 2 and GeSe 4 glasses are determined through density-functional NMR calculations on amorphous model structures generated by ab initio molecular dynamics. The comparison with experimental NMR spectra enables structural assignments for 77Se chemical shifts, pointing to fractional compositions of nearest-neighbor coordinations which are consistent with both neutron diffraction and NMR experiments. © 2011 American Chemical Society.